Broken Embraces - Pedro Almodóvar (2009)
Fourteen years ago, a writer lost his sight and his lover in a car accident, and is now reduced to his pseudonym, Harry Caine. He has completely erased his original identity. Harry lives thanks to the scripts he writes and to the help of her former and always faithful production manager, Judit Garcia, as well as of her son, Diego, who acts as his secretary, typist and guide. But, one night, Diego has an accident and Harry must look after him. In the long night of sitting up with the boy, he tells him of his past as if it was a story. A story portrayed by a photo of a couple of lovers embracing. A photo torn to pieces, resulting in broken embraces.
Keywords: Drama, Romance, Thriller